FACTORS OF INEQUALITY IN MEXICO AND REGIONS: 2000-2010 - Francisco Guillermo Salcido-Vega (Ra Ximhai, 2017)
The aim of the study is to analyze microeconomic foundations with the relationship between inequality and income level, presenting groups and regions of Mexico in 2000-2010. For their properties of decomposition, we use the Jenkins methods, and Gini Exactly by Shapley. To research the database of the household income and expenditure surveys for Mexico were used. It was found that the South-Southeast region has greater inequality and lower per capita income. Is expected to reduce inequality in the regions by education groups, age and gender will improve social welfare.